LOCAL WISDOM BASED ON SOUVENIRS TO INCREASE THE INCOME OF PRAMUKA ISLAND COMMUNITY - Fujianti, Lailah; Wulandjani, Harimurti; Hermawanti, Ati (LPPM Univ. Ibn Khaldun Bogor, 2025)
This Community Service aims to ensure that training participants know that shells in their place which are considered rubbish can be used to craft souvenirs of economic value, can know the steps in making souvenirs from shells, can practice making souvenir crafts made from shells and their benefits. This training is for souvenirs. Service methods include initial survey, preparation, implementation and evaluation. The evaluation results showed that after the training the participants knew that shells which were considered waste up to now could be used as raw material for souvenirs. 84% of participants answered strongly agree and 16% answered agree. After the training, participants knew the steps for making souvenir crafts from shells. 89% of participants answered strongly agree and 11% answered agree. After the training, participants were able to practice how to make souvenir crafts from seashells. 84% of participants answered strongly agree and 16% answered agree, training in making souvenirs from seashells was very useful for Pramuka Island Souvenirs. 94.7% of participants answered strongly agree and % answered agree.